Analysis of the Relevance of Al-Qur'an Learning Materials in Schools with Students' Digital Literacy Needs - Sri Mawarni; Ahmad Nurrohim; Saifuddin Amin (Walidem Institute and Publishing, 2026)
Objective: This study aims to analyze the relevance of Qur'anic learning materials in schools to digital literacy needs, identify challenges and opportunities for technology integration, and provide recommendations for learning strategies that are in accordance with technological developments. Theoretical framework: The theoretical framework of this research refers to digital literacy and technology integration in education. Digital literacy is defined as the ability to utilize technology to support learning, while technology integration aims to improve the quality of education without ignoring the values of religious education. Literature review: This study refers to two main journals. First, Fahmi & Layyinnati discuss the optimization of the digital Qur'an in learning. Second, Lisyawati examine digital literacy in Islamic Religious Education in madrasas. These two studies show the importance of digital literacy to support more effective and relevant religious learning. Methods: The method used was a literature review by analyzing two journals related to the digital Qur'an and digital literacy in Islamic religious education. This analysis aims to explore the relevance and challenges of technology integration in Qur'an learning. Results: The results of the study show that the digital Qur'an can increase learning motivation, expand access to interpretation, and support learning flexibility. However, key challenges include limited infrastructure, teacher readiness, and the risk of exposure to invalid religious information. Implications: The implications of this study show the importance of strengthening digital literacy in learning the Qur'an in schools, as well as the need to improve infrastructure and training for teachers in order to effectively integrate technology in Islamic religious education. Novelty: This research offers a new approach to integrating digital literacy in Qur'an learning, with a focus on the challenges and opportunities of technology integration in the digital age as well as recommendations for relevant learning strategies.